The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.7326/m15-2129
|View full text |Cite
|
Sign up to set email alerts
|

Aspirin for the Primary Prevention of Cardiovascular Disease and Colorectal Cancer: A Decision Analysis for the U.S. Preventive Services Task Force

Abstract: Agency for Healthcare Research and Quality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
99
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 99 publications
(99 citation statements)
references
References 42 publications
0
99
0
Order By: Relevance
“…15 The lower potential net health benefit from aspirin counseling in our analysis is largely a result of the substantially narrowed target population for the service in the current recommendation and the changes to the underlying evidence of aspirin's benefits and harms, including lower expected effectiveness in preventing nonfatal myocardial infarction and stroke-which no longer differ by sex-and accounting for fatalities from aspirin-induced bleeding. 27,32,82,83 This study contributes to a broader evidence base that uses modeling to assess the incremental and comparative effectiveness of clinical services for the primary prevention of CVD. Direct comparisons are often difficult because of differing research questions and methods.…”
Section: Discussionmentioning
confidence: 99%
“…15 The lower potential net health benefit from aspirin counseling in our analysis is largely a result of the substantially narrowed target population for the service in the current recommendation and the changes to the underlying evidence of aspirin's benefits and harms, including lower expected effectiveness in preventing nonfatal myocardial infarction and stroke-which no longer differ by sex-and accounting for fatalities from aspirin-induced bleeding. 27,32,82,83 This study contributes to a broader evidence base that uses modeling to assess the incremental and comparative effectiveness of clinical services for the primary prevention of CVD. Direct comparisons are often difficult because of differing research questions and methods.…”
Section: Discussionmentioning
confidence: 99%
“…Prolonged therapy with low-dose aspirin and aging of the study patients might increase gastrointestinal bleeding caused by aspirin. 36 A previous meta-analysis of hemorrhagic events with aspirin therapy revealed that low-dose aspirin increased the frequency of gastrointestinal bleeding, and comorbidity with diabetes mellitus was a significant risk. 37 A population-based study of aspirin-related bleeding showed that aspirin did not increase gastrointestinal bleeding even in patients with diabetes mellitus, although patients with diabetes mellitus had a higher rate of bleeding than those without diabetes mellitus.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the QRISK lifetime model in the primary prevention setting identifies patients with an unfavorable prognosis at a much younger age than the traditional 10‐year risk approach 11. In addition, recent data demonstrate that treatment benefit estimated in terms of gain in life expectancy was highest in younger patients with otherwise high risk factor levels and was limited in older patients with relatively low risk factor levels in whom remaining survival may be inadequate for meaningful cardiovascular risk reduction to occur 17, 18, 19…”
Section: Introductionmentioning
confidence: 99%